2015
DOI: 10.1177/1062860615583548
|View full text |Cite
|
Sign up to set email alerts
|

Code R

Abstract: In most health care institutions, physician peer review is the primary method for maintaining and measuring physician competency and quality of care issues. However, many teaching hospitals do not have a method of tracking resident trainees' involvement in adverse cases. At the study institution, Code R was introduced as a measure to capture resident trainee involvement in the hospital-wide peer review process. The authors conducted a retrospective review of all peer review cases from January 2008 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In January 2008, we began assigning Code S as well as Code R (resident) designations to our peer reviews, a process we still utilize today. We selected this date range to coincide with our prior Code R study focusing on potential errors involving resident trainees [14]. The study was reviewed by the RUHS Institutional Review Board and was designated a quality improvement project, which did not require formal review.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In January 2008, we began assigning Code S as well as Code R (resident) designations to our peer reviews, a process we still utilize today. We selected this date range to coincide with our prior Code R study focusing on potential errors involving resident trainees [14]. The study was reviewed by the RUHS Institutional Review Board and was designated a quality improvement project, which did not require formal review.…”
Section: Study Protocolmentioning
confidence: 99%
“…In 2008, Riverside University Health System -Medical Center (RUHS-MC) modified its hospitalwide physician peer review process to better capture system errors, an approach that RUHS-MC still uses today. All physician peer reviewers were required to report system errors that may have contributed to an unexpected or adverse event [14]. Code S (for "Systems") designation was given to physician peer review cases that identified a contributing system error(s).…”
Section: Introductionmentioning
confidence: 99%